ANALISIS POTENSI PEMBANGKIT LISTRIK TENAGA MIKRO HYDRO PADA ANAK SUNGAI DI KABUPATEN TULUNGAGUNG - Abbas, Muhammad Luqman Hakim; Kurniawan, Husni Cahyadi (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Indonesia is a country with significant renewable energy potential. One of the sources of renewable energy is the micro-hydro power plant in Tulungagung, an area traversed by large rivers. This study aims to analyze the potential of Micro-Hydro Power Plants (PLTMH) on tributaries in Tulungagung. The research covers 14 rivers in Tulungagung, with location selection based on several criteria. The results indicate that out of the 14 surveyed locations, 10 rivers have the potential to be developed into PLTMH. These rivers include: Srabah River with a capacity of 6.45 kW, Buntaran River with 5.88 kW, Ngranti River with 14.97 kW, Dawuhan River with 7.72 kW, Kalimas River with 39.28 kW, Jajar River with 7.78 kW, Jambu River with 5.35 kW, Ariyojeding River (Lodagung flow) with 248.13 kW, Gilang River with 12.16 kW, Petung River with 12.66 kW. The river with the highest potential and most suitable for a PLTMH is the Aryojeding River, which has the largest capacity at 248.13 kW.